2009
DOI: 10.1016/j.jasms.2009.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Rigorous determination of the stoichiometry of protein phosphorylation using mass spectrometry

Abstract: Quantification of the stoichiometry of phosphorylation is usually achieved using a mixture of phosphatase treatment and differential isotopic labeling. Here, we introduce a new approach to the concomitant determination of absolute protein concentration and the stoichiometry of phosphorylation at predefined sites. The method exploits QconCAT to quantify levels of phosphorylated and nonphosphorylated peptide sequences in a phosphoprotein. The nonphosphorylated sequence is used to determine the absolute protein q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…The use of QconCAT to quantify more than 150 different proteins becomes very expensive costing more than $10,000, as at least three individual QconCAT standards would be needed. In addition, QconCAT is a remarkable method to obtain stoichiometric quantification of multiple proteins since QconCAT peptides are released in strictly equimolar stoichiometry (4,39). The Census Of the Proteome of Yeast (COPY) project is worth mentioning as an example of the application of QconCAT to obtain whole proteome absolute quantification of a minimum of 4,000 proteins in the yeast Saccharomyces cerevisiae (40).…”
Section: Discussionmentioning
confidence: 99%
“…The use of QconCAT to quantify more than 150 different proteins becomes very expensive costing more than $10,000, as at least three individual QconCAT standards would be needed. In addition, QconCAT is a remarkable method to obtain stoichiometric quantification of multiple proteins since QconCAT peptides are released in strictly equimolar stoichiometry (4,39). The Census Of the Proteome of Yeast (COPY) project is worth mentioning as an example of the application of QconCAT to obtain whole proteome absolute quantification of a minimum of 4,000 proteins in the yeast Saccharomyces cerevisiae (40).…”
Section: Discussionmentioning
confidence: 99%
“…In the same year, Eyers et al used the QconCAT method to produce a universal protein standard (QCAL) to calibrate different mass spectrometry platforms for proteomic studies [8]. Johnson et al [9] reported the first application of QconCAT in the quantification of post-translational modifications in 2009, where the absolute amounts of phosphorylated and non-phosphorylated proteins were determined along with stoichiometry of phosphorylation at several predefined sites. An important contribution to the continuous development of QconCAT is the Census Of the Proteome of Yeast (COPY) project, where more than 120 QconCATs have been constructed for large-scale quantification of the Saccharomyces cerevisiae proteome [2].…”
Section: Introductionmentioning
confidence: 99%
“…This increases the sensitivities of the peptides, and may enable the detection of previously undetectable multiply-phosphorylated peptides 23, 25, 26. This technique has been used with both MALDI 13, 24, 25 and ESI 23, 26, 27. Removing the phosphoryl groups has the advantage of facilitating quantitation ā€“ only the relative or absolute abundances of the non-phosphorylated isoforms need to be compared.…”
Section: Introductionmentioning
confidence: 99%